DINAMIKA KEKERASAN DALAM RUMAH TANGGA: TINJAUAN LITERATUR - Kusumawaty, Ira; Yunike, Yunike; Virgonita Iswindari Winta, Mulya (Berajah Journal, 2024)
Domestic violence (DV) is often imagined as women experiencing physical violence, even though not all violence involves physical conditions, because not being injured does not mean experiencing violence. Many women suffer from emotional abuse, which is no less damaging to the victim or her family. This literature review aims to provide a better understanding of the form and impact of coping strategies used by wives of domestic violence victims, and the factors that determine the implementation of their coping strategies. This research can provide a foundation for the development of better interventions. The article search process has been carried out using three databases and the results of the review based on the Critical Appraissal Checklist obtained 12 eligible articles with details of 1 article from Science Direct, 1 article sourced from Google scholar and 10 articles from Scopus indexed journals. Based on the results of the literature review, the coping strategies of wives of domestic violence victims have been identified, the determinants of the form of coping strategies of wives of domestic violence victims, and the impact of coping strategies of wives of domestic violence victims. The results of this study are useful for formulating and developing integrated intervention approaches for victims of domestic violence.